2017
DOI: 10.3389/fncel.2017.00083
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide Nanoparticle-Mediated Forces Enhance the Migration of Schwann Cells Across the Astrocyte-Schwann Cell Boundary In vitro

Abstract: Schwann cells (SCs) are one of the most promising cellular candidates for the treatment of spinal cord injury. However, SCs show poor migratory ability within the astrocyte-rich central nervous system (CNS) environment and exhibit only limited integration with host astrocytes. Our strategy for improving the therapeutic potential of SCs was to magnetically drive SCs to migrate across the astrocyte-SC boundary to intermingle with astrocytes. SCs were firstly magnetized with poly-L-lysine-coated superparamagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 63 publications
3
27
0
Order By: Relevance
“…Subsequent seeding of cells over the unoccupied cell regions would allow for co-culturing of different cell types cell-by-cell or layer-by-layer. Magnetic gradient forces were also reported to support Schwann cell migration through astrocyte-rich cell regions (Figure 3I ) (Xia et al, 2016 ; Huang et al, 2017 ). What remains unclear is how easy magnetic-guided tissue engineering can be applied to primary neurons.…”
Section: Organizing Cell Tissue Constructs With Nano-guidesmentioning
confidence: 88%
“…Subsequent seeding of cells over the unoccupied cell regions would allow for co-culturing of different cell types cell-by-cell or layer-by-layer. Magnetic gradient forces were also reported to support Schwann cell migration through astrocyte-rich cell regions (Figure 3I ) (Xia et al, 2016 ; Huang et al, 2017 ). What remains unclear is how easy magnetic-guided tissue engineering can be applied to primary neurons.…”
Section: Organizing Cell Tissue Constructs With Nano-guidesmentioning
confidence: 88%
“…50,51 Previous studies have reported that cell migration can be enhanced by internalized magnetic nanoparticles in the presence of an MF. 3,31 In the present study, we applied an external MF to SCs after internalization of SPIONs. We firstly showed that the migration ability and migration direction of SCs were not affected by the magnetofection of SPIONs in the absence of an external MF.…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells (SCs), the PNS myelinating glia, perform major functions in creating a favorable environment for axonal growth, stimulating axon outgrowth after injury and rebuilding the myelin sheath of regenerated axons. [3][4][5][6][7][8][9] Therefore, transplantation of SCs has always been considered a feasible method for the repair of nerve injury and functional reconstruction. [10][11][12][13] However, the poor migration of SCs in the astrocyte-rich CNS significantly limits their application in the repair of damaged nerves in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of both proteins generally is connected to advanced stages of cancer. Separately, increased motility speed of Schwann cells (SC), a glial cell in the peripheral nervous system in the presence of SPIONs was reported by Huang et al, however it was only possible when alternating magnetic field was turned on. They observed an enhanced migration along the direction of magnetic field.…”
Section: Effects Of Intracellular Nanoparticles On Adhesion Cytoskelmentioning
confidence: 95%